2016
DOI: 10.1177/1350650116682656
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a finite noncircular floating ring bearing in turbulent flow regime

Abstract: The present paper investigates the turbulence effect on the steady-state performance of a new variety of journal bearing, i.e. the noncircular floating ring bearing. This particular bearing consists of the journal, floating ring, as well as lower and upper lobes. The shaft and the floating ring are cylindrical while surfaces of the bearing are noncircular. The classical Navier–Stokes equations and continuity equation in cylindrical coordinates are being satisfactorily adapted with the linearized turbulent lubr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For the first concept of noncircular FRBs (see Figure 1(b)), Soni and Vakharia 1618 studied its static and dynamic performance using finite element method. However, the nonlinear dynamic response of TC rotor supported by this type of bearings and its ability to reduce the amplitude or suppress sub-synchronous vibrations has not been investigated.…”
Section: Simulation and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the first concept of noncircular FRBs (see Figure 1(b)), Soni and Vakharia 1618 studied its static and dynamic performance using finite element method. However, the nonlinear dynamic response of TC rotor supported by this type of bearings and its ability to reduce the amplitude or suppress sub-synchronous vibrations has not been investigated.…”
Section: Simulation and Discussionmentioning
confidence: 99%
“…For the first concept of noncircular FRBs (see Figure 1(b)), Soni and Vakharia [16][17][18] studied its Table 2. Parameters for run-up simulations.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately the available works on non-circular FRBs are very few, with the exception, to the best of the authors’ knowledge, of the theoretical works of Soni and Vakharia 1921 and the experimental works of Eling et al. 22 Soni and Vakharia 1921 investigated the steady-state and dynamic performance of non-circular FRBs in which the outer bearings of the FRBs are changed in the form of elliptical pattern with finite element method (FEM). The analysis results revealed that the steady-state and dynamic performance of this type of FRBs are superior to the plain cylindrical FRBs.…”
Section: Introductionmentioning
confidence: 99%